2006
DOI: 10.1071/ea04033
|View full text |Cite
|
Sign up to set email alerts
|

Crop stubbles are as important for sheep production as annual pastures in the Victorian Mallee

Abstract: The impact of different management strategies on production and profit can be evaluated with knowledge of how sheep production responds to changes in the available feed base and sheep or pasture management. This study aimed to quantify on-farm pasture and sheep production in mixed sheep and cropping systems in the Victorian Mallee of south-eastern Australia (325 ± 50 mm annual rainfall) as a prelude to computer simulation modelling. During 2001 (average rainfall) and 2002 (extreme drought) pasture production, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…However, given its wide geographic distribution and apparent ability to persist in Mallee cropping systems, spiny M. minima has some value as a pasture species if compared with sub-optimally managed commercial medics. The plant density of commercial medics is usually much lower on farms in the Mallee (<200 plants/m 2 ) (Rigby and Latta 1995) than for the field trials reported here, whereas the density of naturalised stands of spiny M. minima can be higher than that recorded in Experiment 5 (Robertson 2005). The relative densities may be such that M. minima pastures could be as productive as commercial medics under some farm conditions.…”
Section: Productivity Of Species In Fieldcontrasting
confidence: 46%
“…However, given its wide geographic distribution and apparent ability to persist in Mallee cropping systems, spiny M. minima has some value as a pasture species if compared with sub-optimally managed commercial medics. The plant density of commercial medics is usually much lower on farms in the Mallee (<200 plants/m 2 ) (Rigby and Latta 1995) than for the field trials reported here, whereas the density of naturalised stands of spiny M. minima can be higher than that recorded in Experiment 5 (Robertson 2005). The relative densities may be such that M. minima pastures could be as productive as commercial medics under some farm conditions.…”
Section: Productivity Of Species In Fieldcontrasting
confidence: 46%
“…It is the residue left after harvesting using a shearing handpiece . This calibration is based on data from dense improved pastures and contrasts with the residual biomass of 45 3 kg DM/ha after harvest using blade shears in this environment (Robertson 2004). The tests with GrazFeed reported here demonstrate that sheep in this region must be accessing live herbage biomass well below 400 kg DM/ha to achieve the weight gains observed.…”
Section: Discussionmentioning
confidence: 92%
“…Observed herbage biomass from all data sources was assumed to equal total herbage biomass, rather than available herbage, because residual biomass was only reported for 1 data set in this environment (Robertson 2004) which showed that the quantities of residual biomass were not significant.…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the dryland farming systems where wheat and barley are combined with sheep production, regular feed gaps over summer and autumn (Moore et al 2009) are commonly met by feed supplementation. The reliance on supplementary feeding limits farm profitability (Robertson 2006a) and explains low stocking rates and, therefore, low pasture utilisation and resource-use efficiency. With the revitalisation of the grazing component of mixed farming systems due to increasing wool and lamb prices (Bell and Moore 2012), strategies to close the feed gap by differentiating the feed-base are receiving renewed attention (Nichols et al 2007;Dear and Ewing 2008).…”
Section: Introductionmentioning
confidence: 99%